Facile solid-state synthesis for producing molybdenum and tungsten co-doped monoclinic BiVO4 as the photocatalyst for photoelectrochemical water oxidation. (29th March 2019) - Ma, Jia-Sheng; Lin, Lu-Yin; Chen, Yu-Shiang
Abstract: BiVO4 has been widely applied as photocatalysts for water oxidation, owing to preferable band configuration and small band gap for absorbing wide range of light. Synthesizing BiVO4 is usually based on wet routes, which are more complex and require extra steps for separating photocatalysts from solutions. A novel solid-state synthesis is firstly proposed in this study to efficiently synthesize BiVO4 by simply mixing bismuth and vanadium salts without other mediums and directly annealing the mixture at 450°C. Heteroatom-doping of BiVO4 is also achieved by annealing the mixture of W and Mo salts along with bismuth and vanadium precursors to increase the carrier concentration and accelerating the charge transfer. The W and Mo co-doped BiVO4 electrode with the W:Mo ratio of 1:1 shows the highest photocurrent density of 0.21 mA/cm 2 at 1.23 V versus reversible hydrogen electrode and the smallest onset potential of 0.686 V versus reversible hydrogen electrode under air mass 1.5 solar illumination. This study successfully realizes the efficient fabrication of BiVO4 and the incorporation of W and Mo dopants using the solid-state synthesis. Applying this manner cannot only reduce the synthesis time but also provide more precise control of the element composition. Further developments of the co-catalyst/photocatalyst system are expected to be realized by applying this novel solid-state synthesis. Graphical abstract: Image 1 Highlights: Novel solid-state synthesis is used to make BiVO4 as water oxidation photocatalysts. The Bi and V salts are simply mixed and annealed at 450 °C to produce BiVO4 powders. Heteroatom-doping of BiVO4 is got by annealing the mixture of W, Mo, Bi and V salts. The W & Mo co-doped BiVO4 electrode shows photocurrent density of 0.21 mA/cm 2 @1.23 V. Co-catalyst/photocatalyst system is expected to make using the solid-state synthesis.